Ink-jet printed optical waveguides. (26th October 2017) - Bollgruen, P; Wolfer, T; Gleissner, U; Mager, D; Megnin, C; Overmeyer, L; Hanemann, T; Korvink, J G
Abstract: Optical waveguides were fabricated on flexible foil substrates by ink-jet printing, to complement and enhance printed flexible electronics with optical networks. The 145 μ m wide and 20 μ m high transparent polymer tracks were created by printing subsequent tracks of an acrylate ink on polymer foil. A printable, optically transparent material was prepared by a combination of an acrylate resin with a low-viscosity, co-polymerising acrylate. This solved the problem of solvent evaporation for substrates with low heat tolerance. Thermally induced pinning, used to prevent the ink from spreading out on the substrate was achieved by heating the substrate to 60 °C, and found to be strongly affected by the time lapse between deposition of the individual layers. This tool allowed to increase the aspect ratio of the printed tracks from 0.07 to 0.17, and the contact angle of the printed tracks from 15° to 37°. After completion of the deposition step, the waveguides were polymerised under UV light, and covered by a printed upper cladding layer. In the optical evaluation, transmission could be demonstrated with an attenuation in the range of 1.4 dB cm −1 for a wavelength of 785 nm, with a significant portion of material attenuation.